PENDEFINISIAN OBJEK DAN PELENGKAP DALAM KAMUS BESAR BAHASA INDONESIA SEBAGAI PENUNJANG LITERASI - Dewi Puspita; Hermina Sutami (Linguistik Indonesia, 2020)
Literacy cannot be separated from language skills. The most basic language skills are the ability to compose meaningful utterances. For that purpose, a proper understanding of the sentence-forming elements and their functions is needed. Unfortunately, the definitions of the two sentence element functions, namely objects and complements, in KBBI still overlap. The overlapping definition can confuse language users. This paper aims to clarify the differences between object and complement and to correct the inaccuracies in the definition of these two words. Thus, the definition of each of the two functions becomes more appropriate and easily understood by Indonesian language learners. This research was conducted with a functionalism approach through the analysis of syntactic and semantic functions, by paying attention to lexicographic principles. The analysis was carried out on six naturally occurring sentences. The sentences are taken from the Indonesian web corpus. The results of the data analysis in this study indicate that objects and complements are indeed different. From these differences clear and non-overlapping boundaries are obtained.